DETERMINASI PENGUNGKAPAN KEY AUDIT MATTERS DI INDONESIA: BUKTI DARI INDEKS KOMPAS100: DETERMINATION OF DISCLOSURE OF KEY AUDIT MATTERS IN INDONESIA: EVIDENCE FROM THE COMPASS100 INDEX - Ferizqi, Luthfi; Reskino, Reskino (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
This study examines the relationship between audit committee, financial industry, audit firm, firm size to key audit matters (KAM) in Indonesia. A disclosure index approach is employed from the International Standard on Auditing (ISA) 701 and a regression run on a population of Kompas100 Index for the first implementation year in 2022. The hypothesis was assessed utilizing the Multiple Linear Statistical Test, with the analysis performed at a significance level of 0.05. The results of regression analysis indicate that the size of audit committee significantly influences KAM disclosures. A statistically insignificant relationship was found between the financial industry, audit firm, firm size and KAM. The research acknowledges the existence of a positive and statistically significant correlation between the characteristics of the audit committee, financial industry, choice of audit firm, firm size, and the disclosure of KAM within the country. This study also reports the empirical results of the first-time implementation of KAM, such as auditor market share, as well as the number of KAM topics disclosed. The results revealed that the number of reported KAM in Indonesia is significantly lower compared to neighboring countries such as Singapore. Regulatory bodies in Indonesia, could conduct further analysis to determine whether the current enhancement auditor's report is adequate and meets investor expectations. This research improves our understanding of the extent of KAM disclosure and the specific factors in Indonesia, thereby improving the knowledge of policymakers and decision-makers regarding KAM disclosure in audit reports.